Factors associated with diphtheria vaccination completion among children under five years old in Peru 2010–2019: A cross-sectional population-based study - Gonzales, Antony (2022)
The World Health Organization (WHO) recommends a minimum of 90% coverage of diphtheria three-dose complete vaccination scheme (DPT) as part of routine immunization programs in children. However, diphtheria coverage in Peru has not reached the minimum recommended during the last decades. Our study aimed to determine the complete three-dose DPT coverage and factors associated with compliance towards complete vaccination in Peru between 2010-2019. We conducted a secondary cross-sectional study using the “Encuesta Demogr afica y de Salud Familiar (ENDES)”- Demographic and Family Health Survey, which is a survey that targets mothers between 15 and 49 years of age. DPT vaccination coverage was 72.4% and several factors were associated with the DPT scheme completion. Women in the age groups 18 to 24 (ORa ¼ 2.31, 95%CI: 2.11–2.52), 25 to 34 (ORa ¼ 3.37, 95% CI: 3.08–3.69), and 35 to 49 (ORa ¼ 4.74, 95% CI: 4.29–5.22) were more likely to complete their children's DPT vaccination scheme compared to those between 15 to 17 years of age. Both Spanish (ORa ¼ 1.39, 95% CI: 1.31–1.48) and Quechua (ORa ¼ 1.34, 95% CI: 1.25–1.43) as first spoken language were associated with DPT completion compared to native language speaking mothers. Women who worked (ORa ¼ 1.72, 95% CI: 1.57–1.88), studied (ORa ¼ 1.47, 95% CI: 1.33–1.62), or were housewives (ORa ¼ 1.41, 95% CI: 1.29–1.54) during the previous week were more likely to complete their children's DPT scheme compared to participants that did not work during the previous week. Women with the financial capability to access health care were less likely to complete the DPT scheme (ORa ¼ 0.95, 95% CI: 0.92–0.97). Considering the accessibility to health care centers, women who knew the nearest location (ORa ¼ 1.07, 95% CI: 1.03–1.11), had geographic accessibility (ORa ¼ 1.09, 95% CI: 1.06–1.13) or a current transport (ORa ¼ 1.06, 95% CI: 1.02–1.09) were more likely to complete their children ‘s DPT scheme. Our results highlight low diphtheria vaccine coverage levels in Peru, with values lower than what is recommended by the WHO. Results may serve as a baseline for future studies to improve vaccination programs, reduce barriers and increase DPT coverage in Peru.